SSF 1371 : A new spiny safflower variety for rainfed and irrigated conditions of India: SSF 1371 : A new spiny safflower variety for rainfed and irrigated conditions of India - L N TAGAD; S K SHINDE; S V KHADTARE; D R MURUMKAR; V B AKASHE; K C OMBASE (Journal of Oilseeds Research, 2020)
SSF 1371 is a spiny variety derived through pedigree selection method from the cross Bhima x NARI 44. In the multi-location trials, SSF 1371 recorded 9.84% and 17.47 higher yield over the checks A1 and PBNS 12, respectively.It has also recorded 14.98% and 18.67% higher oil yield over the check A1 and PBNS 12, respectively. Oil content of SSF 1371 was 29.2%. It was responsive to higher doses of fertiliser and late sown conditions. It was identified during 2019 for cultivation in Maharashtra, Karnataka and Telangana states.